“As soon as I start trusting human beings, they disappoint me, and now I am going to get on an app that someone could hack. I really do not want to take that chance”: barriers and facilitators to digital peer support implementation into community mental health centers - Fortuna, Karen L.; Divatia, Shreya; Neupane, Sudeep; Geiger, Pamela; Bohm, Andrew (Frontiers in Digital Health, 2023)
Background Certified peer support specialists often use technologies such as smartphone applications to deliver digital peer support in community mental health centers. Certified peer support specialists are individuals with a mental health diagnosis, trained and accredited by their state to provide mental health support services. Digital peer support has shown promising evidence of promoting recovery, hope, social support, and medical and psychiatric self-management among patients with a diagnosis of a serious mental illness. Interest in digital peer support as part of the patient experience has grown. Understanding barriers and facilitators to the implementation process of digital peer support into community mental health centers is a critical next step to facilitate uptake. Methods Semi-structured qualitative interviews were conducted with 27 patient participants (N = 17 persons with serious mental illness; N = 10 certified peer support specialists) from an urban community mental health center. Participants responded to open-ended questions on the barriers and facilitators of engaging with digital peer support technologies within community mental health centers. The interview guide and the responses were categorized according to the Consolidated Framework for Implementation Science Research (CFIR) constructs. Results Nine barriers and two facilitators were identified for the implementation of digital peer support in community mental health centers. The overarching domains for the identified barriers included (1) intervention characteristics (i.e., adaptability, complexity, and cost), (2) inner settings (i.e., implementation climate, readiness for implementation, and access to knowledge and information), and (3) characteristics of individuals (i.e., knowledge and beliefs about the intervention and other personal attributes). The two facilitators identified included (1) intervention characteristics (i.e., relative advantage) and (2) outer setting (i.e., patient needs and resources). Conclusions The identified barriers and facilitators represent a starting point for developing or modifying digital peer support technology requirements to ease implementation in community mental health centers. Building technology requirements and implementation processes based on these findings may facilitate uptake of digital peer support technologies by people with serious mental illness and certified peer support specialists in community mental health centers.